Prevention and treatment of radiotherapy-induced oral mucositis: a literature review - Albuquerque, Iêda Lessa de Souza (2007)
The prevention and treatment of radiotherapy-induced oral mucositis have still not been fully defined. The current study thus involved a literature search aimed at identifying preventive and therapeutic measures in relation to oral mucositis in patients submitted to radiotherapy, analyzing the level of evidence in the selected studies, identifying which indications for prevention and treatment in the literature pertain to the field of nursing, and critically analyzing the results and their implications for nursing care. This was a systematic literature survey without a metaanalysis, consulting the following databases: Bireme, Medline, CancerLit, Scirus, CAPES, Free medical journal, Highwire press, Scielo, and Medscape, from 2000 to 2005. According to observations, nursing care was capable of improving patient's quality of life, promoting education of patients, implementing and supervising oral care programs, and providing guidance on hygiene, prevention, and treatment of oral mucositis, including pain management. However, no Brazilian nursing publications were found on the subject. Research and publications focusing on nursing experience in the prevention and treatment of radiotherapy-related oral mucositis and the implications for patients and nurses are important to provide evidence-based nursing guidelines.